2020
DOI: 10.22219/kinetik.v5i1.896
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale Entropy and Multiclass Fisher’s Linear Discriminant for Emotion Recognition Based on Multimodal Signal

Abstract: Emotion recognition has been special topics which are frequently discussed by researchers and practitioners in the past decade. SpO2 and Pulse rate signals are two of the limited physiological signals used in a study of emotion recognition. In this study, both of the physiological signals were utilized for emotion recognition in elders by using a combination of two feature extraction methods. Multiscale Entropy was used for feature extraction of signals and then reduced dimension of the feature vector by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
0
0
1
Order By: Relevance
“…An increase in accuracy scores using combined features in classification was also shown in the study conducted by Hakim et al in recognizing or detecting emotions based on Pulse Rate and SpO2 signals [15] using the Support Vector Machine method. This finding indicated that using combination features is recommended for classification to develop precise object detection or identification systems.…”
Section: Feature Extraction Resultssupporting
confidence: 55%
“…An increase in accuracy scores using combined features in classification was also shown in the study conducted by Hakim et al in recognizing or detecting emotions based on Pulse Rate and SpO2 signals [15] using the Support Vector Machine method. This finding indicated that using combination features is recommended for classification to develop precise object detection or identification systems.…”
Section: Feature Extraction Resultssupporting
confidence: 55%
“…Ada banyak rumus jarak yang digunakan dalam algoritma kNN. Pada penelitian ini menggunakan rumus jarak Euclidean dalam mencari jarak terdekat karena berdasarkan beberapa literatur menyebutkan rumus jarak ini paling powerful dibandingkan dengan rumus jarak lainnya [9]- [12]. Rumus jarak Euclidean didapatkan dengan menggunakan persamaan berikut:…”
Section: Klasifikasiunclassified